Peran Guru PAK dalam Merancang Pembelajaran yang Mengintegrasikan Iman dan Kehidupan Siswa (Jurnal Pendidikan Agama dan Teologi, 2024)
Christian Religious Education (PAK) has an important role in forming students' character and faith by prioritizing the application of Christian teachings in everyday life. PAK teachers not only focus on teaching theological doctrine, but also provide guidance to students in applying the values ​​of faith in every decision and social relationship. By using a creative, relevant and technology-based approach, Christian Religious Education (PAK) teachers are able to overcome various challenges faced, such as negative influences from the environment and limited student understanding. In this way, they are able to create a learning process that inspires and strengthens student character. The role of PAK teachers includes implementing learning strategies based on Bible stories, critical discussions, real action projects, and the use of technology. This aims to link the concept of faith with life values. Barriers such as limited resources and minimal student involvement can be overcome by using an inclusive and interactive approach. PAK teachers inspire students to understand and apply Christian values, forming individuals with strong characters who are responsive to social demands.